1998
DOI: 10.1021/la980497e
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of Polyionic Layer-by-Layer Films Containing Azobenzene

Abstract: In this work we employed the layer-by-layer adsorption technique for deposition on solid substrates of polyionic films containing photoactive azobenzene groups. We investigated two systems, each having the same polyanion but using a different polycation. Poly {1-4[4-(3-carboxy-4-hydroxyphenylazo)benzenesulfonamido]-1,2-ethanediyl sodium salt} (PAZO) was employed as the photoactive polyanion; poly(diallyldimethylammonium chloride) (PDDA) and poly(ethyleneimine) (PEI) were used as the polycations. Our phenomenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
153
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 46 publications
13
153
0
Order By: Relevance
“…The silanol groups at the surface of glass and quartz, as well as of silicon wafers due to the thin surface layer of oxide, can be easily deprotonated by base. Treatment with various functionalized silanes, such as trialkoxy-3-aminopropylsilane 113,114,143,200,219,227,286,388,395) , provides an additional, "easy" access to positively charged surfaces. In a similar way, treatment of gold with functionalized thiols or disulfides, respectively, enables the tailoring of both positively (e. g. when applying cysteamine 119,211,277,296,387) ) or negatively (e. g. when applying mercaptoundecanoic acid 115,116,228,269,286,396,397) ) charged surfaces.…”
Section: Useful Substratesmentioning
confidence: 99%
“…The silanol groups at the surface of glass and quartz, as well as of silicon wafers due to the thin surface layer of oxide, can be easily deprotonated by base. Treatment with various functionalized silanes, such as trialkoxy-3-aminopropylsilane 113,114,143,200,219,227,286,388,395) , provides an additional, "easy" access to positively charged surfaces. In a similar way, treatment of gold with functionalized thiols or disulfides, respectively, enables the tailoring of both positively (e. g. when applying cysteamine 119,211,277,296,387) ) or negatively (e. g. when applying mercaptoundecanoic acid 115,116,228,269,286,396,397) ) charged surfaces.…”
Section: Useful Substratesmentioning
confidence: 99%
“…21 The effect of polycation type-branched poly͑ethyleneimine͒ and linear poly͑diallyldimethylammonium chloride͒-on the orientation of the azo group in polycation/poly͕1-͓p-͑3Ј-carboxy-4Ј-hydroxyphenylazo͒benzenesulfonamido͔-1,2-ethandiyl͖ ͑PCBS͒ LbL films was studied using absorbance measurements although NLO effects were not probed. 22 A lyotropic, cationic polyionene and strong polyanions were used to make highly ordered films consisting of up to 50 bilayers, but SHG was not studied. 23 In most of these studies where film thickness was measured, it was found that the film thickness and chromophore content-the latter characterized by absorbance measurements-scaled linearly with the bilayer number.…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation and photochemical behavior of the azo chromophore (absorbance spectrum, isomerization rate, etc.) vary depending on the nature of the counterpolymer (Dante et al, 1999) (and of course, is affected by any ionic ring substituent). These may be viewed as undesirable matrix effects, or as a way to tune the chromophore response.…”
Section: Polyelectrolyte Multilayersmentioning
confidence: 99%